TAXES AND "SOCIAL COSTS" (Tufts Archival Research Center, 2007)
Draft; Report describing the trend of increasing tobacco excise taxes. Discusses the debate between the tobacco industry and governmental agencies, who are raising taxes to finance deficits and health care reform. States objectives of the report, including showing that excise taxes are detrimental and regressive as well as responding to anti-smokers' arguments "social cost" arguments. Emphasizes that excise taxes should not be the answer to funding health care.